2019
DOI: 10.3389/fcell.2019.00342
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-coding RNA Maternally Expressed 3 Increases the Expression of Neuron-Specific Genes by Targeting miR-128-3p in All-Trans Retinoic Acid-Induced Neurogenic Differentiation From Amniotic Epithelial Cells

Abstract: MicroRNA (miR)-128-3p is a brain-enriched miRNA that participates in the regulation of neural cell differentiation and the protection of neurons, but the mechanisms by which miR-128-3p regulates its target and downstream genes to influence cell fate from adult stem cells are poorly understood. In this study, we show down-regulation of miR-128-3p during all-trans retinoic acid (ATRA)-induced neurogenic differentiation from amniotic epithelial cells (AECs). We investigated miR-128-3p in both the Notch pathway an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…However, the reports about lncRNAs in PD is relatively less. Accumulation research have indicated that lncRNAs serve as miRNAs “sponges” to influence gene expression base on the ceRNA regulation theory 18‐20 . lncRNA SNHG1 sponges miR‐15b‐5p triggers SIAH1 activation and further leads to α‐synuclein aggregation and neurotoxicity 21 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the reports about lncRNAs in PD is relatively less. Accumulation research have indicated that lncRNAs serve as miRNAs “sponges” to influence gene expression base on the ceRNA regulation theory 18‐20 . lncRNA SNHG1 sponges miR‐15b‐5p triggers SIAH1 activation and further leads to α‐synuclein aggregation and neurotoxicity 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Accumulation research have indicated that lncRNAs serve as miRNAs "sponges" to influence gene expression base on the ceRNA regulation theory. [18][19][20] lncRNA SNHG1 sponges miR-15b-5p triggers SIAH1 activation and further leads to α-synuclein aggregation and neurotoxicity. 21 Likewise, RAB3IP induces HOTAIR acts as a sponge of miR-126-5p aggravates the progression of PD.…”
mentioning
confidence: 99%
“…The lncRNA MEG3 is upregulated by the cAMP/response element-binding protein (CREB) pathway to increase the expression of neuron-specific genes and act as a ceRNA, influencing the expression of miR-128-3p [ 82 ].…”
Section: Lncrnas From Stem and Progenitor Cells To Neuronsmentioning
confidence: 99%
“…Meg3 positively modulates neural markers, by acting as a sponge for miR-128, which in turn represses β-III tubulin, neuron-specific enolase (NSE) and polysialic acid neural cell adhesion molecule (PSA-NCAM) mRNA levels. The de-repression of these neuron-specific genes by Meg3 promotes and increases the number of neurons, suggesting a critical role for this lncRNA in neural differentiation and nervous system development [ 114 ]. Similar to Meg3 , Hotairm1 is upregulated by RA in a differentiation context, i.e., granulocytic differentiation.…”
Section: Role Of Lncrnas As Ra Mediated Differentiation Drivermentioning
confidence: 99%